In vitro antioxidant activity of Lantadene A - Chong Grace-Lynn; Ibrahim Darah; Sasidharan Sreenivasan (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Lantadenes are the pentacyclic triterpenoids present in the leaves of the plant Lantana camara. Pentacyclic triterpenes are often studied as their biological properties are considerable and contributes to the development of modern therapeutic drugs. In recent years various natural product based compounds are extensively studied for various pharmacological activities including antioxidant activity. Therefore, this study aims to determine the in vitro antioxidant activity of Lantadene A (from Lantana camara ) as results will enhance the knowledge of the compound towards development of hepatoprotective agents. The antioxidant assays performed on the compound were the DPPH radical scavenging assay, nitric oxide assay, superoxide anions scavenging activity and iron chelating assay. Results showed promising antioxidant activities as the IC50 for Lantadene A in the above assays were 6.574 mg/ml, 0.098 mg/ml, 2.506 mg/ml and 0.001 mg/ml respectively as compared to the standards (BHT, ascorbic acid and EDTA) 0.027 mg/ml, 0.075 mg/ml, 1.025 mg/ml and 0.47 mg/ml respectively. The DPPH radical scavenging assay for Lantadene A was weaker than BHT while iron chelating assay of Lantadene A is much stronger than the standard. The rest of the assays were comparable to the reference standards. These results suggest that Lantadene A can be a potential cadidate to be developed as an antioxidant.